Flipped Learning with Google Classroom in Improving Learning Outcomes and Independent Attitudes - Datuk Dwi Saputro; Rusnilawati (Jurnal Pendidikan dan Pengajaran, 2023)
The application of the flipped learning model can improve student learning outcomes. This study aims to analyze the effectiveness of the application of the flipped learning model assisted by Google Classroom media in improving student learning outcomes and independence in solving social studies questions. This research is quantitative research with quasi-experiments. The population in this study were all students of an elementary school. While the sample in this study were 40 students of class V at one of the elementary schools. The research instruments used were test questions and student independence questionnaires. Researchers used validity and reliability tests on research instruments before being used in research. The prerequisite test results show that the data obtained is normally distributed and homogeneous. The data analysis technique used is the dependent t-test and the Manova test. Based on the results of the analysis, it was obtained: t-count > t-table, namely 4,918 > 1,685, so there is a difference in the use of the flipped learning model with the help of Google Classroom in improving student social studies learning outcomes; t-count > t-table, namely 6.972 > 1,685, there is a significant difference in independent attitude after applying the model flipped learning with the help of google classroom compared to before implementing; a significance value of 0.000 <0.05, there is a significant difference in learning outcomes and independent attitudes after implementing the flipped learning model with the help of google classroom compared to before implementing.